All‐Printed Roll‐to‐Roll Perovskite Photovoltaics Enabled by Solution‐Processed Carbon Electrode - David Beynon (Advanced Materials, 2023)
Perovskite photovoltaics have shown great promise in device efficiency but also the promise of scalability through solution-processed manufacture. Efforts to scale perovskites have been taken through printable mesoporous scaffolds and slot die coating of flexible substrates roll-to-roll (R2R). However, to date there has been no demonstration of entirely R2R-coated devices due to the lack of a compatible solution-processable back electrode; instead, high-value evaporated metal contacts are employed as a post process. Here, in this study, the combination of a low-temperature device structure and R2R-compatible solution formulations is employed to make a fully R2R printable device architecture overcoming interlayer incompatibilities and recombination losses. Therefore, the n–i–p device structure of SnO2/perovskite/poly(3,4-ethylenedioxythiophene)/carbon is employed to form an ohmic contact between a p-type semiconductor and printable carbon electrode. In particular, the results show that the small-scale device efficiencies of 13–14% are achieved, matching the device performance of evaporated gold electrodes. Also, this entirely R2R-coated perovskite prototype represents a game changer, reaching over 10% (10.8) stabilized power conversion efficiency with unencapsulated long-term stability retaining 84% of its original efficiency over 1000 h under 70% RH and 25 °C.